Exergy analysis of offshore primary petroleum processing plant with CO2 capture. (August 2015) - Carranza Sánchez, Yamid Alberto; de Oliveira, Silvio
Abstract: Primary petroleum processing operations in offshore platforms require significant quantities of energy for extraction, processing and transport. In offshore platforms, these energy requirements are usually provided by locally produced gas, and gas turbines are widely used to generate electricity required for operational activities such as driving pumps and compressors. Releases of gaseous emissions are an integral and inevitable part of the process and CO2 -emissions occur mainly from the combustion of gas for power generation and heating purposes. This paper presents the formulation and simulation to evaluate the exergy performance of the processes in an offshore platform considering two configurations: with and without CO2 capture system. Exergy balance formulations have been used to assess the performance of the configurations. Simulations have been developed using Aspen HYSYS ® . The exergy consumption required for the petroleum heating in the separation process has a noticeable influence on the whole plant irreversibility. Exergy analysis results are useful to assess and identify processes with potential to improve the plant efficiency and its environmental performance. Highlights: Exergy performance of an offshore platform without and with CCS is evaluated. Exergy efficiency and Renewability exergy index were used to assess the performance. Separation train has a remarkable influence on the whole plant irreversibility. Exergy efficiency decreases when 77% of CO2 emissions are avoided. Renewability exergy index has a slight increment when CCS is implemented.